Review article: the therapeutic potential of 5-HT3 receptor antagonists in the treatment of irritable bowel syndrome. - Humphrey, P; Bountra, C; Clayton, N; Kozlowski, K (Blackwell Publishing Ltd., 1999)
There is evidence from studies, in both animals and humans, that 5-HT3 receptor blockade has potential value in the treatment of irritable bowel syndrome, particularly in those patients with diarrhoea-predominant bowel habits. New findings suggest that 5-HT3 receptors exist on gut afferent neurones and that their activation by locally released 5-HT leads to visceral nociceptive stimulation, in addition to increased neuronally-mediated motor and secretory activity. If this concept is validated, it will provide a rationale for the use of 5-HT3 receptor antagonists in patients with increased gut motility, reduced fluid absorption and low nociceptive thresholds leading to abdominal pain. Alosetron is a highly selective, potent 5-HT3 receptor antagonist which is well absorbed with a long pharmacodynamic half-life. Its ability to provide long-lasting blockade of 5-HT3 receptors throughout the body make it an ideal candidate within its class to evaluate the clinical hypothesis that sustained and ubiquitous 5-HT3 receptor blockade is of value in the treatment of IBS.